2017
DOI: 10.1039/c7nr04464j
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Co2P nanoflowers assembled from nanorods for ultralong cycle-life supercapacitors

Abstract: Hollow CoP nanoflowers (CoP HNFs) were successfully prepared via a one-step, template-free method. Microstructure analysis reveals that CoP HNFs are assembled from nanorods and possess abundant mesopores and an amorphous carbon shell. Density functional theory calculations and electrochemical measurements demonstrate the high electrical conductivity of CoP. Benefiting from the unique nanostructures, when employed as an electrode material for supercapacitors, CoP HNFs exhibit a high specific capacitance, an out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 64 publications
2
31
1
Order By: Relevance
“…The high‐resolution P 2p spectra (Figure d, Figure S8e) of Co 2 P and Ni 12 P 5 are very similar. The doublets at 129.3 and 130.2 eV are assigned to P−Co or P−Ni, while the broad peak at 133.3 eV originates from the oxidized P species . The slight surface oxidation is a common phenomenon of TMP nanomaterials as a result of air contact, and is consistent with many other reports …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The high‐resolution P 2p spectra (Figure d, Figure S8e) of Co 2 P and Ni 12 P 5 are very similar. The doublets at 129.3 and 130.2 eV are assigned to P−Co or P−Ni, while the broad peak at 133.3 eV originates from the oxidized P species . The slight surface oxidation is a common phenomenon of TMP nanomaterials as a result of air contact, and is consistent with many other reports …”
Section: Resultssupporting
confidence: 90%
“…For Co 2 P, the characteristic peaks of Co-P corresponding to Co 2p 3/2 and Co 2p 1/2 appear at 777.9 and 792.8 eV, respectively. [30] Two satellite peaks at 785.6 and 802.5 eV and the peaks at 781.2 (2p 3/2 ) and 797.1 eV (2p 1/2 ) arise from Co À O bonding in oxidized Co species. [31] Ni 12 P 5 exhibits similar electron states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, Cheng et al. synthesised the Co 2 P hollow nanoflower structure and reported a high specific capacitance of 412.7 F g −1 at 1 A g −1 . Likewise, Elshahawy et al.…”
Section: Introductionmentioning
confidence: 99%
“…So far, Cheng et al synthesised the Co 2 P hollow nanoflower structure and reported a high specific capacitance of 412.7 F g À 1 at 1 A g À 1 . [23] Likewise, Elshahawy et al have grown CoP nanowires array on carbon cloth and reported the specific capacity of ∼ 165.82 mAh g À 1 at 1 A g À 1 in 6 M KOH electrolyte. [24] Similarly, Zhang et al have testified the synthesis of the mesoporous CoP nanowire arrays on carbon cloth and exhibited a high areal capacitance (1.89 F cm -2 at 3 mA cm À 2 ) and excellent cycling stability (∼ 3% loss after the repetitive 4000 cycles at 18 mA cm À 2 ).…”
Section: Introductionmentioning
confidence: 99%